Criminal caution and conviction rates for children who were supported at different tiers of the care system and those who had a special educational need - Leyland, Anna; Hughes, Nathan; Webb, Calum; Bennett, Matthew (International Journal of Population Data Science, 2025)
Objectives The presentation will give an overview of a project exploring criminal justice system outcomes for children who were supported at different tiers of the care system, detailing local authority differences in outcomes, and differences for children who also had a special educational need. The presentation will include sharing the data dashboard and other practice and policy facing outputs from this project. Method The data used was the linkage between the NPD and PNC covering birth years 1995-1998. The analyses were multilevel and multivariate logistic regression models. Care system involvement was the highest tier of intervention recorded in the data, from referral only, child in need, child protection plan, and looked after child. Analysis was for any criminal caution or conviction, and custodial sentences. Results Children with any involvement with the care system are 2-4 times more likely to have a criminal caution or conviction by early adulthood, compared to children outside of the care system. Care involved girls experience a greater risk of offending relative to girls without care system involvement, when compared to boys with/without care experience. The risk of a custodial sentence was higher for all care experienced children, but girls faced greater risk related to their care system involvement than boys. Rates of care system involved youth with a criminal caution or conviction were up to three times higher in some local authorities compared to other local authorities, regardless of area poverty and general offending rates. Children with an SEN were more likely to have a criminal caution or conviction and custodial sentence in both the non-care and care populations, but being a care involved child with an SEN further increased risk of poor outcomes. Conclusions Children at every tier of the care system are more likely to have a caution or conviction than children outside of the care system. This disadvantage varies across the Local authorities in England and is greater for those with additional needs.